The "New" Student-Athlete - Claire C. Schaeperkoetter; Jonathan Mays; Sean Thomas Hyland; Zach Wilkerson; Brent Oja; Kyle Krueger; Ronald Christian; Jordan R. Bass (University of Kansas Libraries, 2017)
The growth and popularity of eSports cannot be understated. The domain has become so mainstream that colleges and universities are rapidly beginning to launch eSports programs within their athletics departments. In this study, the authors interviewed 33 student-athletes receiving scholarships for participating in eSports at one institution. In all, the identity and social capital of athletes in this "new" athletic arena were explored and compared with previous studies examining "traditional" athletes. The implications of the similarities and differences are discussed and ideas for future research into this emerging field are presented.